1996
DOI: 10.1073/pnas.93.15.7849
|View full text |Cite
|
Sign up to set email alerts
|

An essential regulatory role for macrophage migration inhibitory factor in T-cell activation.

Abstract: The protein known as macrophage migration inhibitory factor (MIF) was one of the first cytokines to be discovered and was described 30 years ago to be a T-cellderived factor that inhibited the random migration of macrophages in vitro. A much broader role for MIF has emerged recently as a result of studies that have demonstrated it to be released from the anterior pituitary gland in vivo. MIF also is the first protein that has been identified to be secreted from monocytes/macrophages upon glucocorticoid stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
572
3
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(603 citation statements)
references
References 28 publications
19
572
3
9
Order By: Relevance
“…In normal lungs, MIF is constitutively expressed by the bronchial epithelium, alveolar macrophages and capillary endothelium [27,30]. A prominent induction of MIF mRNA and protein has been observed in activated Th2 cells, while eosinophils have pre-formed MIF and are able to secrete high quantities of it upon stimulation [28,31]. A role of MIF on Th2 pathologies has been demonstrated by the inefficient control of helminthic infection in the absence of MIF [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal lungs, MIF is constitutively expressed by the bronchial epithelium, alveolar macrophages and capillary endothelium [27,30]. A prominent induction of MIF mRNA and protein has been observed in activated Th2 cells, while eosinophils have pre-formed MIF and are able to secrete high quantities of it upon stimulation [28,31]. A role of MIF on Th2 pathologies has been demonstrated by the inefficient control of helminthic infection in the absence of MIF [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…5A). Previous studies have shown that MIF regulates the activation of T cells induced by mitogenic or antigenic stimuli, inducing IL-2 secretion and lymphocyte proliferation [31,34]. In fact, MIF -/-mice have a reduced spleen T cell-proliferative response upon OVA restimulation [34].…”
mentioning
confidence: 99%
“…7,8 There are several lines of evidence supporting the MIF gene as a good candidate in inflammatory disorders, such as SLE. 9 MIF plays a critical role in regulation of T-cell activation, and it has been demonstrated that alterations in this pathway lead to the development of SLE in animal models 10 MIF may provide signals for B-cell proliferation that could maintain the hyperactivity of B cells showed in SLE patients. 11 MIF might also contribute to the chronic inflammatory injury in SLE, due to, induction of proinflammatory cytokines, such as interleukin (IL)-1b, tumor necrosis factor a (TNF-a), IL-2, IL-6, IL-8 and interferon g (IFN-g), which seem to be associated with the severity of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…MIF is essential for T cell activation and possibly contributes to maintaining Th1/Th2 imbalance as described above [1]. Also, a prominent increase in systemic MIF levels was detected in patients with severe AD, and the levels decreased when the clinical symptoms improved following treatment with corticosteroid ointment [18,19].…”
Section: Introductionmentioning
confidence: 84%
“…Macrophage migration inhibitory factor is considered to act by both paracrine and autocrine stimulatory pathways to augment the activation of these cells [15]. As reported previously, MIF is essential for T cell activation and possibly contributes to maintaining Th1/Th2 imbalance [1]. Increased MIF expression has been reported in lesions from many immune/ inflammatory diseases, including psoriasis, glomerulonephritis, transplant rejection, neuro-Behçet's disease, asthma, adult respiratory distress syndrome, and inflammatory eye diseases [3,4,7,11,12,13,16,17,20,24].…”
Section: Introductionmentioning
confidence: 84%